Spectral absorbtance of gaseous propylene - D. V. Kosenkov; V. V. Sagadeev; V. A. Alyaev (Известия высших учебных заведений: Проблемы энергетики, 2017)
Discusses the results of experimental studies of the function of the spectral transmittance of propylene at high pressures and temperatures.